South African Universities and the Question of Decolonization - Wolff, Ernst (Interreligious studies and intercultural theology, 2021)
This article brings together reflections on the recent debates regarding the decolonization of philosophical and social scientific curricula at South African universities. This context is outlined, and the specificity of philosophy as a vantage point is explained. Thereafter four dilemmas are outlined as constitutive of university practices beyond the limits of South African university philosophy: (1) the relative importance of local and Western legacies, (2) weighing the positive and negative potential of the ambiguous Western traditions and their reception, (3) distinguishing what is relevant in any tradition to our work in the present and (4) the politics of the rights and freedoms of divergent role players to participate legitimately in these debates. I describe these four issues as core to our ongoing struggles for finding appropriate ways to work in universities "after Bandung".